Socratic dialogue in the story by Vasyl Shevchuk «The Teacher of Truth»: communicative and pragmatic arrangement of the speech act (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article deals with the research of the narrative and compositional model of the Socratic dialogue (SD), that contains both secondary (philosophical conversation, controversy) and primary speech genres (representatives, confirmation, negation, refutation etc.) The topic of the SD has been analyzed in the story by Vasyl Shevchuk “The Teacher of Truth”. It has been found out that two narrative and compositional models are presented in the work – the instructive dialogue, which realizes the speaker’s communicative intention to teach the addressee the dialectical method of search for truth, and the examinational dialogue, that realizes the addresser’s aim to identify what wisdom involves, who is wise and who is not. The composition of the Socratic dialogue is formed within generic features of philosophical conversation: introduction, dialogization of philosophical logos, the end of dialogical communication. Compositional blocks of the SD present the content and sense unity, the focus of which is a dialogue of the communicator’s heteropolar approaches to a philosophical or a moral and ethical theme for establishment of the truth. This part of the SD is the most dynamic and at the same time consistent in the development of the philosophical logos. The initiation of the philosophical dialogical discourse belongs to the addresser in the form of the speech act (SA) of question. The microevent of “search for truth by logical methods” is formed by the addresser’s communicative move, that consists of two steps – the SA of agreement and the SA of question, and a reaction move in the form of agreement, representative, constative, negation. The declaration of partial results of search for truth also belongs to the addresser. The adjacency pair of the dialogical discourse in the speech genre of controversy is formed by the addressee’s beginning move in the form of the SA of confirmation, implicit or explicit negation and the addresser’s reaction move expressed by the SA of negation, refutation, constative, representative, accusation. The microevent of «talker’s admission of his lack of knowledge» is given in the form of the SA of agreement and assumption, allowance and disapproval, accusation. The logical definition of the notion (the first narrative model of the SD) is given in the form of the SA of representative (extended statement-sentence). The conclusion about the essence of wisdom, who is wise and who is not (the second narrative model of the SD) is expressed by the SA of constative and confirmation.
Keywords: dialogical discourse; speech act; speech genre; Socratic dialogue; controversy; philosophical conversation